A race to the bottom in labor standards?: an empirical investigation - Davies, Ronald B.; Vadlamannati, Krishna Chaitanya (Journal of development economics, 2013)
One of the concerns over globalization is that as nations compete for investment, they relax labor standards to attract firms. Using spatial estimation on panel data for 135 countries over 17years, we find that the labor standards in one country are positively correlated with those elsewhere (i.e. a cut in labor standards in other countries reduces labor standards in the country in question). This interdependence is more evident in labor practices (i.e. enforcement) than in labor laws. Further, while we find evidence of competition in both developed and developing countries, it is strongest among developing countries with weak standards.
Gesehen am 10.12.2020
Keywords: OECD